إيكاندو لتعلم اللغة العربية عند الطفولة المبكرة في عصر الرقمنة 5.0 (Icando) استخدام (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2023)
This research is motivated by an early childhood child whose educational tendencies are based on games, so this study aims to describe the Icando Platform for learning Arabic in early childhood. The research was conducted using a qualitative approach, and the source of the data came from Arabic teachers. Data were collected through observation techniques, interviews, and documentation studies. The result of the study is that Icando is an interesting educational Platform for early childhood; with this Platform they can play to learn Arabic. The researchers recommend further developing the use of various forms of Platforms that support the implementation of education in difficult conditions. The limitation of this study is that it can be carried out and its effectiveness has not been studied comprehensively, therefore this aspect has not been discussed in this study in the future work of researchers.
Keywords: Icando; early childhood; Arabic language learning